2021
DOI: 10.3389/fonc.2021.648873
|View full text |Cite
|
Sign up to set email alerts
|

Canine Parvovirus and Its Non-Structural Gene 1 as Oncolytic Agents: Mechanism of Action and Induction of Anti-Tumor Immune Response

Abstract: The exploration into the strategies for the prevention and treatment of cancer is far from complete. Apart from humans, cancer has gained considerable importance in animals because of increased awareness towards animal health and welfare. Current cancer treatment regimens are less specific towards tumor cells and end up harming normal healthy cells. Thus, a highly specific therapeutic strategy with minimal side effects is the need of the hour. Oncolytic viral gene therapy is one such specific approach to targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 102 publications
0
7
0
Order By: Relevance
“…The CPV-2 NS1 protein has remained relatively conserved during the process of virus evolution. It is a phosphorylated protein with multiple functions, such as inducing apoptosis and promoting oncolysis [ 4 , 5 , 6 ]. The VP2 gene is 1755 bp in length and encodes 584 amino acids.…”
Section: Introductionmentioning
confidence: 99%
“…The CPV-2 NS1 protein has remained relatively conserved during the process of virus evolution. It is a phosphorylated protein with multiple functions, such as inducing apoptosis and promoting oncolysis [ 4 , 5 , 6 ]. The VP2 gene is 1755 bp in length and encodes 584 amino acids.…”
Section: Introductionmentioning
confidence: 99%
“…, 2009 ). CPV-induced oxidative stress is mediated through damage of mitochondrial membrane, non-structural protein 1 (NS1) induced DNA damage besides liberation of pro-inflammatory cytokines ( Arora et al. , 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…NS1 is the largest non structural protein in CPV-2, and it is primarily involved in viral replication and pathogenicity [22]. NS1 is a key mediator of cytotoxicity of CPV and can selectively cause tumor cell lysis by inducing an antitumor immune response in different tumor models [23]. A recent study demonstrated the amino acid residues of T598 and T601 in the C-terminal phosphorylation sites of NS1 protein, involved in replication and pathogenicity of CPV-2 [24].…”
Section: Virology Of Cpv-2mentioning
confidence: 99%